MEKANISME PENGELOLAAN PAJAK PENGHASILAN KARYAWAN PADA PT. POS INDONESIA REGIONAL V SURABAYA - Firdaus, Anita; Kustini, Kustini (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Income Tax Article 21 withholding at PT Pos Indonesia Regional V Surabaya is carried out directly by the Human Resources (HR) division, where the tax withheld is part of the benefits provided by the company to employees. With the implementation of the new policy from the Directorate General of Taxes (DGT), the tax withholding procedure must be changed to align with the latest regulations. In this community service activity, the author provides information and training to the HR department regarding the PPh 21 withholding procedure in accordance with the latest regulations. The methods applied include counseling, discussion, and simulation of income tax calculations for employees. The results of this activity show an increase in the understanding and skills of human resources in implementing withholding and reporting taxes appropriately and accurately. This activity helps companies to comply with taxes and reduces the possibility of administrative errors that can result in tax sanctions. It is hoped that this socialization activity can be an example for other BUMN companies in managing employee income tax effectively and in accordance with existing regulations.